Exploring industrial tourism's potential: How can it contribute to business innovation? - Montenegro, Z.; Marques, J.; Sousa, C. (Proceedings of the 18th European Conference on Innovation and Entrepreneurship (ECIE 2023), 2023)
This article delves into the potential of industrial tourism and emphasizes its significance as an innovative and sustainable product for industrial companies. The research question driving this exploration is, "How can industrial tourism contribute to business innovation?" In answering this question, the article provides valuable insights into the development of strategies that allow companies to leverage industrial tourism for their benefit, ultimately positioning it as a strategic factor for enhancing their competitiveness. As part of an ongoing research project, the study adopts the Delphi research methodology and presents the initial findings from the first round of questionnaires administered to a panel of 27 experts. The results demonstrate that industrial tourism can act as a catalyst for innovation within industrial companies, making a notable impact across various areas, including Operations, Marketing, and Human Resources. Moreover, the findings indicate that generating additional income, prioritizing environmental and social integrity, and preserving industrial heritage is closely associated with innovation through industrial tourism. The research underscores the pivotal role of the Financial, Operational, and Human Resources areas within industrial companies for the successful diversification into industrial tourism. However, the strategic alignment of the company's overall vision with industrial tourism is equally fundamental. Despite not being the primary focus of industrial companies, industrial tourism emerges as a potent source of innovation and competitiveness within these organizations. The results suggest that the Financial, Operational, and Human Resources areas of industrial companies are central to the success of diversification to Industrial Tourism. Still, it is fundamental that the company strategy is aligned with industrial Tourism. Although Industrial Tourism is not the focus of industrial companies, it can be a source of innovation and competitiveness within companies.